USULAN PERBAIKAN PADA PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI PT. SURYA TOTO INDONESIA TBK DIVISI SANITARY DENGAN METODE HIRA DAN FTA - Fatma, Nur Fadilah; Putra, Dhimas Eka Mustafa (Journal Industrial Manufacturing, 2021)
Identification of potential hazards and risk assessments are part of the occupational safety and health program in the risk management stage, which is conducted in an effort to prevent work accidents and occupational illness. The purpose of this research is to identify the potential hazard in PT Surya Toto Indonesia Tbk Sanitary division and analyze the root cause and give suggestion of improvement. Location and time of observation is PT Surya Toto Indonesia Tbk in April until May 2017. Object of observation is potential danger in section Slip Preparing PT Surya Toto Indonesi Tbk. The methods used by the researchers are HIRARC and FTA. The identification of potential hazards and risk assessments undertaken by researchers together with experts, which in this case are OSH officers and local supervisors, resulted in 25 different risks. With the following division, 2 low risk level, 10 medium level risk, 11 high risk level and 2 extreme level risk. After handling by the management of the company against the risk of extreme and high level, there is risk to be 2 high risk and 11 medium level risks. To reduce the value of risk, companies can make safer working conditions and better supervision of employee's unsafe behavior. Keywords: Hazard Potential Identification, Risk Assessment, SMK3, HIRARC, FTA